BIOCHEMICAL ADAPTION OF PHOTOSYNTHETIC ENZYMES TO CHEMICAL AND ENVIRONMENTAL VARIATIONS. (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
Photosynthesis is not only a metabolic pathway but also an adaptive biochemical mechanism. Plant survival depends on the ability of photosynthetic enzymes to adjust to fluctuations in chemical and environmental conditions. Enzyme plasticity allows plants to maintain metabolic balance despite variations in nutrient supply, temperature, and carbon dioxide concentration.The catalytic function of photosynthetic enzymes follows the principles of enzyme kinetics. Reaction velocity increases with substrate concentration until enzyme saturation occurs. However, excessive oxygen concentration may promote photorespiration, reducing carbon fixation efficiency. Thus, the balance between CO₂ and O₂ plays a critical regulatory role.  Mineral nutrients contribute directly to enzyme synthesis and stability. Nitrogen is a structural component of amino acids and proteins, including RuBisCO. Iron participates in electron transfer reactions within photosystem I. Manganese is essential for water-splitting reactions in photosystem II. Deficiency of these elements disrupts enzymatic reactions and lowers photosynthetic productivity. Photosynthetic enzymes also respond to intracellular redox signals. The thioredoxin system regulates enzyme activation in response to light intensity. This reversible regulation ensures that energy production matches carbon assimilation demands.